INVESTIMENTO SOCIOAMBIENTAL CORPORATIVO: A BUSCA POR UM MODELO DE SELEÇÃO DE PROJETOS SUSTENTÁVEIS - Lopes, Nícolas Castro (2010)
When selecting socio-environmental projects to be financed, the concern with their sustainability has been a constant. Choosing a project that is not sustained can result in wasting the company s resources and causing future problems. This work aims to come up with key issues for the selection of effective projects that can bring lasting results. The research will make use of theoretical reference and the most renowned companies and organizations expertise performing in Social Responsibility. The result was an analytical framework that supports the definition of criteria for selection of projects according to the main factors that stand for risks to its sustainability.